On the Back of La Bestia: Violence Against Migrants in Transit through Mexico - Herrera Mejía, Leonardo (2025)
Mexico is traveled by thousands of migrants, mostly Central Americans in search of the “American dream”, many of them board freight trains, risking their lives. Added to this risk is the violence inflicted on them by the authorities, police, criminals, organized crime and inhabitants of different communities. Two causes of said violence are analyzed. The first is that migrants have become economic loot, that is, the commodification of humans. This occurs as a result of the second cause, the construction of an otherness, in two senses, on the one hand, a growing xenophobia induced and on the other the disqualification as humans, an act that leads to abuses against them.